الطريقة السمعية الشفهية وتطبيقها في تعليم اللغة العربية - Shofwatul Fu'adah; Nur Agung; Agus Nu’man (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
The Sam’iyah Syafahiyah or Audiolingual method arose in the fifties of the twentieth century as a of applying the doctrine of foreign language learning with the aim to helping American officers and soldiers acquire the languages ​​of the peoples who were fighting them during war in quick and fruitful ways. Then this method developed rapidly and was used in language learning in the world including in learning English and Arabic language. This method is a combination of behaviorism theory in psychology and structural theory in linguistics and based on a structural approach in language teaching. The purpose of this method is to master the four language skills of listening, speaking, reading and writing. This is not much different from other language teaching methods, however the principle of this method is to teach speaking skills before writing